Shear strength of residual soil under infiltration conditions - Wong, Joo Chai. (2008)
Two major laboratory tests were conducted. Constant suction shearing tests performed to investigate the unsaturated behaviour of residual soils and shearing-infiltration tests to simulate the stress path followed by a soil element in residual soil slope during rainfall.